Ethical judgments: what do we know, where do we go? - Mudrack, Peter E.; Mason, E. Sharon (My University, 2014)
Investigations into ethical judgments generally seem fuzzy as to the relevant research domain. We first attempted to clarify the construct and determine domain parameters. This attempt required addressing difficulties associated with pinpointing relevant literature, most notably the varied nomenclature used to refer to ethical judgments (individual evaluations of actions' ethicality). Given this variation in construct nomenclature and the difficulties it presented in identifying pertinent focal studies, we elected to focus on research that cited papers featuring prominent and often-used measures of ethical judgments (primarily, but not exclusively, the Multidimensional Ethics Scale). Our review of these studies indicated a preponderance of inferences and conclusions unwarranted by empirical evidence (likely attributable at least partly to inconsistent nomenclature). Moreover, ethical judgments related consistently to few respondent characteristics or any other variables, emergent relationships may not always be especially meaningful, and much research seems inclined to repetition of already verified findings. Although we concluded that knowledge about ethical judgments seems not to have advanced appreciably after decades of investigation, we suggested a possible path forward that focuses on the content of what is actually being judged as reflected in the myriad of vignettes used in the literature to elicit judgments.
Keywords: Ethical judgments; Literature review; Vignettes